(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The article outlines the essence of the concept of the educational environment, reveals its structure, and clarifies its key role in the system of future primary school teachers’ training. To meet that aim, several theoretical methods, including analysis of sources and literature on the research; structural and functional to justify the structure, content, and principles of building a training system; and theoretical modeling, are utilized. The interconnected components of the researched professional training have been described. They provide a positive result for the professional development of the future primary school teacher: axiological, socio-cultural, epistemological, cognitive, creative, personal-activity, and communicative. It has been proved that the educational environment design utilizing art synthesis allows: for more accurately predicting and controlling the teaching process, solving educational and training tasks, ensuring favorable conditions for the development of creative personality, and optimal use of available resources.